PENGARUH METODE LIFE KINETIK TERHADAP KONSENTRASI DAN PERFORMA BERMAIN STRIKER PADA CABANG OLAHRAGA SEPAKBOLA - Ilham Abi Gunawan, - (2021)
The study discussed how Life Kinetic methods affect Concentration and the Performance of Striker on the Football Branch. The purpose of this study is to know how life kinetic methods affect concentration and the performance of striker's play on the football branch. The method used is the method of experimentation. The population is striker striker from the menpora west Java trophy of 25 athletes. The sample from the collected jocks is approximately 10 with random sampling cluster techniques.The instrument used to measure the concentration skills of striker's athletes is a concentration test by filling up the concentration grid test (CGT) and for measuring the performance of striker using a performance test using of the Game Performance Assessment Instrument (GPAI). The results of this study suggest that life's kinetic methods for concentration and the performance of striker's play on the football branch had a significant impact. Keywords : Life Kinetik, Concentration, Performance, Football Striker